BALANCED NUTRITION PROGRAM: IMPROVING THE QUALITY OF LIFE OF PEOPLE THROUGH A HOLISTIC NUTRITION POLICY - Loso Judijanto; Rosdiana; Entin Solihah (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Nutritional balance plays an important role in supporting public health and economic development. Previous studies have shown an association between good nutrition and improved cognitive performance and work productivity, as well as reduced prevalence of non-communicable diseases. The research method used in this study was literature review. The results show that increasing access to nutritious food has a significant impact on reducing the rates of chronic diseases such as diabetes and hypertension. Furthermore, school-integrated nutrition programs have been shown to improve children's attendance and academic performance. From an economic perspective, improved nutritional status is directly related to increased labor productivity.